CORPORATE SOCIAL RESPONSIBILITY AND PROSPECTS FOR SOCIAL PROJECT MANAGEMENTOF ENTERPRICES - Beketova Kamar Nazarbekovna; Abdimomynova Almakul Shakirbekovna (Scientific Journal of Pedagogy and Economics, 2021)
The concept of social responsibility is the result of the evolution of traditional views on the nature of management due to the assessment of the organization’s activities impact on the external environment; an approach that has shown its effectiveness and efficiency over decades of practice. Along with the contribution of environmental issues to the formation of socially responsible behaviors, a significant contribution to the development of this concept is the revision of the organizations image and their place in society, understanding the hidden power over the formation of favorable economic conditions and defining the complex motives that determine their philanthropic inclinations. In modern conditions the concept of social responsibility is one of the most important strategic management tools used to maintain the competitiveness of the enterprise, it is used in enterprises to assess and plan activities that contribute to the harmonious development of internal and external social environment.